2012
DOI: 10.6064/2012/205027
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Obesity and Associated Metabolic and Cardiovascular Disorders

Abstract: Obesity has significant implications for healthcare, since it is a major risk factor for both type 2 diabetes and the metabolic syndrome. This syndrome is a common and complex disorder combining obesity, dyslipidemia, hypertension, and insulin resistance. It is associated with high atherosclerotic cardiovascular risk, which can only partially be explained by its components. Therefore, to explain how obesity contributes to the development of metabolic and cardiovascular disorders, more and better insight is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 201 publications
(204 reference statements)
1
33
0
Order By: Relevance
“…Meanwhile, TNF-α activates CD4 + Th 1 cells and CD8 + effector T cells, leading to proinflmmatory macrophage stimulation (Holvoet, 2012;Lafontan, 2014). This study found that RAW 264.7 macrophages treated with exosomes isolated from ob/ob mice led to higher production of IL-6 and TNF-α when compared to +/+ mice.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Meanwhile, TNF-α activates CD4 + Th 1 cells and CD8 + effector T cells, leading to proinflmmatory macrophage stimulation (Holvoet, 2012;Lafontan, 2014). This study found that RAW 264.7 macrophages treated with exosomes isolated from ob/ob mice led to higher production of IL-6 and TNF-α when compared to +/+ mice.…”
Section: Discussionmentioning
confidence: 65%
“…During obesity, adipocytes secrete exosomes, which are absorbed by monocytes, and the monocytes further migrate into adipose tissues and differentiate into macrophages (Hajer et al, 2008;Holvoet, 2012). Meanwhile, TNF-α activates CD4 + Th 1 cells and CD8 + effector T cells, leading to proinflmmatory macrophage stimulation (Holvoet, 2012;Lafontan, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations